2023
DOI: 10.3390/cells12030356
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Exosomes in Human Carcinogenesis and Cancer Therapy—Recent Findings from Molecular and Clinical Research

Abstract: Exosomes are biological nanoscale spherical lipid bilayer vesicles, 40–160 nm in diameter, produced by most mammalian cells in both physiological and pathological conditions. Exosomes are formed via the endosomal sorting complex required for transport (ESCRT). The primary function of exosomes is mediating cell-to-cell communication. In terms of cancer, exosomes play important roles as mediators of intercellular communication, leading to tumor progression. Moreover, they can serve as biomarkers for cancer detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 131 publications
0
14
0
Order By: Relevance
“…sEVs are natural nanosized vesicles and have immense potential for drug delivery [ 24 ]. miR-497/TP-HENPs are bioinspired hybrid nanoparticles characterized by nano size, good drug encapsulation effectiveness, and protection of nucleic acids, which can stably and continuously release miR-497 and suppress OC chemotherapy resistance both in vivo and in vitro [ 110 ].…”
Section: Sev and Ocmentioning
confidence: 99%
See 1 more Smart Citation
“…sEVs are natural nanosized vesicles and have immense potential for drug delivery [ 24 ]. miR-497/TP-HENPs are bioinspired hybrid nanoparticles characterized by nano size, good drug encapsulation effectiveness, and protection of nucleic acids, which can stably and continuously release miR-497 and suppress OC chemotherapy resistance both in vivo and in vitro [ 110 ].…”
Section: Sev and Ocmentioning
confidence: 99%
“… Principles and applications of sEVs in cancer therapy. ( a ) sEV contents induce chemo [ 14 ], radiation [ 16 ], and targeted therapy resistance [ 17 ] by changing the sensitivity of recipient cells through intercellular communication; ( b ) sEVs can regulate angiogenesis [ 17 , 18 ] and vascular permeability [ 19 , 20 ] by influencing the behavior of endothelial cells that line blood vessels; ( c ) sEVs can regulate the evasion [ 21 ] and infiltration [ 22 ] of immune cells by stimulating or suppressing immune responses, that is, they have the ability to act as immunomodulators [ 23 ]; ( d ) direct incubation of sEVs with cargo [ 24 ] or sEVs with surface engineering [ 25 ] can achieve the function of therapeutic cargo packing and targeted therapy (Created with (accessed on 26 February 2023)). …”
Section: Figurementioning
confidence: 99%
“… 47 , 48 , 49 In recent studies, exosomes have received attention because of their potential functions and as next-generation drug delivery vehicles in various diseases. 50 , 51 , 52 , 53 Furthermore, various substances can be carried as cargo by exosomes for delivery to treat human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes can include many cellular components, including nucleic acids, lipids, proteins, etc., which can provide rich omics information, such as cell genome, transcriptome, proteome, and metabolome information ( 6 , 7 ). Increasing evidence has indicated that exosomes are closely related to tumor formation, growth and metastasis and the acquisition of drug resistance ( 8 , 9 ). Additionally, the regulatory function of exosomes in tumors is related to nucleic acids and is mediated by the horizontal transfer of proteins ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%